Herencia – Spanish as a heritage language: - Antonia Castañeda (Revista Espaço Acadêmico, 2021)
Though often not recognized, Spanish is a heritage language for a significant part of the United States, including Florida, Louisiana, Texas, and the Western states carved out of the Mexican cession after the U.S.-Mexico War in 1848. The California state constitution of 1849, for example, stipulated that “All laws, decrees, regulations and provisions which from their nature require publication, shall be published in English and Spanish”. Yet thirty years later, when California re-wrote its state constitution in 1879, it passed an “English-only” law requiring English-only instruction in the public schools and eliminated Spanish language rights. In 1918 — during the era of WWI xenophobia and fears about the loyalty of non English speakers — Texas, and a majority of other U.S. states, enacted statutes that made the speaking of any language other than English on public school grounds illegal. English-only laws were the bedrock of “Americanization schools” and programs in educational and other institutions.